SERVANT LEADERSHIP, SELF AWARENESS DAN KOMPENSASI PENGARUHNYA TERHADAP EMPLOYEE ENGAGEMENT DAN KINERJA KARYAWAN PADA PUSKESMAS TANJUNGBUMI MADURA - Taufiqur Rachman; Siti Mujanah; Nanis Susanti (STIE Mahardhika, 2021)
The purpose of this study was to examine the effect of Servant Leadership, Self Awareness and Compensation on Performance and Employee Engagement at Tanjungbumi Health Center, Bangkalan Regency. The sample used in this study were 107 respondnets non-medical personnel who were submitted the questionairs from 125 population. The data was collected by distributing a questionnaire with several statements. While the technical data analysis used in this study is to use Partial Least Square (PLS). The results of this study are as follows: the increase in Servant Leadership, Self Awareness and Compensation has significantly increase the employee's Engagement. Moreofer Servant Leadership, and Self Awareness significantly influence to the Employee Performance,, but Compensationh has no effect on increasing employee performance; Neverthelse an increase in Employee Engagement will significantly influence the increase in Employee Performance. This implay that to increase employee performance to improve performance can be done by increasing servant leadership, self awareness and compensation given to employees